Critical thinking level of nurses in management technique catheterization in the emergency services, hospitalization, medical and surgical Vitarte Hospital - Barboza Núñez, Luz Yanet (2019)
Objective: Determine the level of critical thinking of nursing professionals in the art of managing bladdercatheterization in the emergency services, hospitalization, medical and surgical Vitarte Hospital. Material andMethods: The research design was quantitative, descriptive, cross-sectional. The sample consisted of 45 nurses(I) emergency services (25), hospital medicine (12) and surgery (8) Vitarte Hospital. Using the instrument,“Critical Thinking Questionnaire,” which consisted of 39 specific questions, the same that was validated byexperts. Reliability test was 0,803 according to the Cronbach alpha coefficient. Results: The study showed that100% of the sample, 64.4% of nurses, reaches an average level of critical thinking in management techniquecatheterization. As for the eight dimensions covered by the study, it appears that in perceptual acuity and constantquestioning, reach an average level of critical thinking with 55.6% and 57.8%, respectively, while in intellectualcourage, open mind, self-regulation, emotional control and fair assessment, achieved a high level of criticalthinking with 53.3%, 84.4%, 71.1%, 53.3% and 80.0%, respectively, finally, in construction and reconstructionof knowledge, 66.7% had a low level of critical thinking in management technique catheterization. Conclusions:The level of critical thinking of nursing professionals in the art of managing bladder catheterization, is average.